PENGARUH MINAT DAN LITERASI TEKNOLOGI TERHADAP PENGGUNAAN DOMPET DIGITAL - Ahmad Setiadi Hasir; Abdul Muis Mapalotteng; Anas Arfandi (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This study aims to determine: (1) the effect of interest in using digital wallets on the use of digital wallets among students at Makassar State University; (2) the effect of digital technology literacy on the use of digital wallets among students at Makassar State University; (3) the effect of interest and digital technology literacy on the use of digital wallets among students at Makassar State University. The type of research used is quantitative using the survey method. The sample in this study were 400 students at Makassar State University. Data collection techniques using questionnaires and documentation techniques. The data were analyzed using descriptive statistical analysis, prerequisite analysis, and hypothesis testing. The results showed that; (1) there is an influence of interest on the use of digital wallets in students at Makassar State University; (2) there is an influence of technological literacy on the use of digital wallets in students at Makassar State University; (3) there is an influence of interest and technological literacy together on the use of digital wallets in students at Makassar State University